2018
DOI: 10.1016/j.vetmic.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Helicobacter and Campylobacter species in faecal samples from zoo mammals

Abstract: Helicobacter and Campylobacter species (spp.) colonize the gastrointestinal tract of various domesticated animals. Apart from their pathogenic significance in animals, several species are of zoonotic importance as well. For most non-domesticated animal spp., however, little is known on the presence and importance of these agents. Therefore, we investigated the presence of Helicobacter and Campylobacter spp. in marine and terrestrial zoo mammals. Faecal samples of various marine and terrestrial zoo mammals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Non-H. pylori species can infect both humans and animals, and their probable transmission between humans and animals might serve as a reservoir for the transmission of pathogenic microorganisms to Available at www.veterinaryworld.org/Vol.13/September-2020/21.pdf human contacts [11]. In vitro cultivation of the gastric non-H. pylori species organisms is extremely difficult and cannot be exclusively used for diagnostic purposes, which necessitates different techniques for the diagnosis of Helicobacter infections [7][8][9][10][11][12]. In the present study, using PCR, we identified the presence of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Non-H. pylori species can infect both humans and animals, and their probable transmission between humans and animals might serve as a reservoir for the transmission of pathogenic microorganisms to Available at www.veterinaryworld.org/Vol.13/September-2020/21.pdf human contacts [11]. In vitro cultivation of the gastric non-H. pylori species organisms is extremely difficult and cannot be exclusively used for diagnostic purposes, which necessitates different techniques for the diagnosis of Helicobacter infections [7][8][9][10][11][12]. In the present study, using PCR, we identified the presence of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriological culturing is the preliminary step in most of the recent studies conducted on tabulating the prevalence and characterization of Campylobacter spp. in captive animals or wildlife . Despite being able to obtain campylobacter isolates from a higher number of animals after repeated sampling, the overall rate of recovery of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…have been routinely isolated from both primate zoological collections, non‐human primates used for research, and those living in the wild . In particular, C jejuni has been commonly isolated bacteria from zoological collections . Campylobacter jejuni has been studied extensively in cotton‐top tamarins, a species belonging to the same genus as Geoffroy's tamarins, and association between C jejuni, diarrhea, and mortality in cotton‐top tamarins has been noted in isolated cases .…”
Section: Discussionmentioning
confidence: 99%
“…28 This suggests that pet-associated gastric Helicobacters cause little or no harm in their natural host, which is in contrast to other members of the NHPH group. 31 Another study also reported Helicobacter species in the stomach of aquatic marine mammals, for example, East Asian finless porpoises (Neophocaena asiaeorientalis sunameri), and to a lesser extent in the foregut, hindgut, and feces. 31 Another study also reported Helicobacter species in the stomach of aquatic marine mammals, for example, East Asian finless porpoises (Neophocaena asiaeorientalis sunameri), and to a lesser extent in the foregut, hindgut, and feces.…”
Section: Pre S En Ce Of Non -H Elicobac Ter Pylori Helicobac Ter S mentioning
confidence: 96%
“…29 However, Takemura et al 30 Furthermore, novel enterohepatic Helicobacter species were identified in both marine and terrestrial zoo mammals. 31 Another study also reported Helicobacter species in the stomach of aquatic marine mammals, for example, East Asian finless porpoises (Neophocaena asiaeorientalis sunameri), and to a lesser extent in the foregut, hindgut, and feces. 32 Proliferative and invasive colorectal tumors were investigated in 20 pet dogs.…”
Section: Pre S En Ce Of Non -H Elicobac Ter Pylori Helicobac Ter S mentioning
confidence: 96%